Associations of novel serum lipid index with epithelial ovarian cancer chemoresistance and prognosis - Li, Yuan; Shang, Chunliang; Liang, Huamao; Zhang, Kun; Wu, Yu; Guo, Hongyan (Frontiers in Oncology, 2023)
Purpose : To evaluate the relationship between novel serum lipid index and chemoresistance as well as prognosis of epithelial ovarian cancer (EOC). Patients and Methods: Patients’ serum lipid profiles of 249 cases diagnosed with epithelial ovarian cancer, including total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C) as well as their ratios, the novel indicators HDL-C/TC and HDL-C/ LDL-C, and clinicopathologic characteristics were retrospectively collected and calculated from January 2016 to January 2020 and correlation between serum lipid index and clinicopathological features such as chemoresistance as well as prognosis were evaluated. Results : 249 patients pathologically diagnosed EOC who underwent cytoreductive surgery were included in our cohort. Binary logistic regression analyses indicated Federation International of Gynecology and Obstetrics (FIGO）stage and HDL-C/TC ratio had significant association with chemoresistance. Univariate analyses demonstrated pathological type, chemoresistance, FIGO stage, neoadjuvant chemotherapy, maintenance treatment, HDL-C/LDL-C ratio, HDL-C/TC ratio were related to Progression-Free Survival (PFS) and Overall Survival (OS) (P<0. 05). Particularly, multivariate analyses indicated that HDL-C/LDL-C ratio was independent protective factors for both PFS and OS. Conclusion : The complex serum lipid index HDL-C/TC ratio has a significant correlation with chemoresistance. HDL-C/LDL-C ratio is closely related to the clinicopathological characteristics and prognosis of patients with EOC and is an independent protective factor indicating better outcome.